2021
DOI: 10.1002/anie.202016437
|View full text |Cite
|
Sign up to set email alerts
|

Rules of Nucleophilic Additions to Zigzag Nanographene Diones**

Abstract: Nucleophilic addition of carbon-centered nucleophiles to nanographene ketones represents avaluable late-stage method for the functionalization of zigzag nanographenes,but its use is rare in the chemical literature.U sing two model systems,non-KekulØ triangulene-4,8-dione and KekulØ anthanthrone,w ei dentify unexpected regioselectivities and uncover the rules that govern these reactions.C onsidering the large number of nanographene ketones that have been reported since the pioneering work of Eric Clar,this meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…The introduction of mesityl groups to the carbonyl carbons of 3 was then examined. The use of mesityllithium as the nucleophile did not produce the desired addition product 4 due to the nucleophilic attack at the α-carbon in a 1,4-addition manner . This undesired side reaction was effectively suppressed by employing mesityllithium in combination with either CeCl 3 or LaCl 3 ·2LiCl, , and we found that the use of LaCl 3 ·2LiCl was more operationally simple and reproducible.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The introduction of mesityl groups to the carbonyl carbons of 3 was then examined. The use of mesityllithium as the nucleophile did not produce the desired addition product 4 due to the nucleophilic attack at the α-carbon in a 1,4-addition manner . This undesired side reaction was effectively suppressed by employing mesityllithium in combination with either CeCl 3 or LaCl 3 ·2LiCl, , and we found that the use of LaCl 3 ·2LiCl was more operationally simple and reproducible.…”
Section: Resultsmentioning
confidence: 78%
“…The use of mesityllithium as the nucleophile did not produce the desired addition product 4 due to the nucleophilic attack at the α-carbon in a 1,4-addition manner. 25 This undesired side reaction was effectively suppressed by employing mesityllithium in combination with either CeCl 3 26 or LaCl 3 •2LiCl, 27,28 and we found that the use of LaCl 3 •2LiCl was more operationally simple and reproducible. Demethylation and dehydration of 4 using trifluoroacetic acid proceeded with the concomitant migration of a hydroxy group to give 5 in 80% yield over two steps from 3.…”
Section: ■ Introductionmentioning
confidence: 80%
“…The first attempt towards this goal was reported by Juríček et al in 2021. 53 In this approach ( Scheme 6 ), the first substituent in the center of one edge was installed by means of the Suzuki cross-coupling reaction of 3,5-di- tert -butylphenylboronic acid and TOT triflate. The resulting monosubstituted triangulene-4,8-dione displays a significantly improved solubility compared to the unsubstituted dione, which is practically insoluble.…”
Section: šOlomek and Juríček's Attempt (2021)mentioning
confidence: 99%
“…The 4,10-diphenyl substituted anthanthrone (Ph-AT) was prepared by Suzuki coupling of VO3 with phenylboronic acid in a yield of 87 %. [50,51] Polymer PAT-Ph was synthesized in a similar way as Ph-AT by using the bifunctional 1,4-phenylenebisboronic acid instead. Notably, all synthetic processes are simple, scalable, and merely use inexpensive chemical feedstocks.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%